Tantangan Kebijakan Pemanfaatan Sampah Sebagai Solusi Sumber Energi Listrik Dalam Upaya Pengurangan Emisi Karbon di Indonesia - Budi Hermawan; Muhammad Fadhil; Andi Shufiyah Qulub; Inas Affazul Muna; Si Yusuf Al Hafiz (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
PLTSa is an alternative solution to reducing waste and carbon emissions, however, the construction of PLTSa still causes problems so how can the policy of using waste as a source of electrical energy be implemented in Indonesia's efforts to reduce carbon emissions? This research is included in normative juridical research which focuses on using secondary data: primary and secondary legal materials. Based on the data used in this research, literature research uses a conceptual approach, a statutory approach, and a case approach. The research found that although PLTSa can be an alternative for dealing with waste and renewable energy problems, the construction of PLTSa installations as a source of electrical power still has social and environmental consequences and risks. Current waste management policies regard waste as useless waste rather than a resource that must be utilized. Therefore, it is important to pay greater attention to the use of PLTSa as a power generator in the environment, especially by paying attention to the quality standards for dioxins and furans produced by PLTSa.